Distribution, Metabolism, and Excretion of Gedatolisib in Healthy Male Volunteers After a Single Intravenous Infusion. Issue 1 (26th September 2018) - Houk, Brett E.; Alvey, Christine W.; Visswanathan, Ravi; Kirkovsky, Leonid; Matschke, Kyle T.; Kimoto, Emi; Ryder, Tim; Obach, R. Scott; Durairaj, Chandrasekar
Abstract: In this open‐label study (NCT02142920), we investigated the distribution, pharmacokinetics, and metabolism of the pan‐class‐I isoform phosphatidylinositol 3‐kinase/mammalian target of rapamycin inhibitor gedatolisib (PF‐05212384), following a single intravenous administration in healthy male subjects. A single, 89‐mg, intravenous dose of gedatolisib was associated with a favorable safety profile in the 6 healthy subjects evaluated. Peak plasma concentrations for unchanged gedatolisib and total radioactivity were observed at the end of the 30‐minute infusion. The only observed drug‐related material in plasma was the parent drug, gedatolisib. Terminal half‐life for plasma gedatolisib was ∼37 hours. Following the dose, 66%–73% of drug‐related material was recovered in the feces. Metabolism of gedatolisib was trace; only 1 oxidative metabolite, M5, was identified in feces (<1% of total dose). Identification of gedatolisib in feces suggests that biliary and/or intestinal secretion of unchanged parent drug significantly contributes to gedatolisib clearance.